Evaluation of RME Implementation Based on Digital Maturity Index (DMI) in the Digital Transformation Stages of Healthcare at Muhammadiyah University Malang Hospital - Hanafiah, Ali; Oktoriani, Ervita Nindy; Puspita , Dyah Rangga (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to evaluate the implementation of Electronic Medical Records (EMR) at the General Hospital of Muhammadiyah University Malang (RSU UMM) based on the Digital Maturity Index (DMI) in the context of healthcare digitalization transformation. This research employs the Hospital Information System Maturity Model (HISMM) to measure the digital maturity level of RSU UMM. The research method utilized includes surveys and observations involving medical, administrative, and managerial staff directly engaged in the use of EMR. The results indicate that the digital maturity level at RSU UMM is at 65.3%, suggesting that while the EMR implementation is progressing well, improvements are still needed in several indicators such as Data Analysis, Strategy, Information Security, and Human Resource Management. Factors influencing the successful implementation of EMR include technological readiness, managerial support, user training, and data security policies. This evaluation is expected to assist RSU UMM in enhancing the efficiency and effectiveness of healthcare services by optimizing the EMR system and accelerating the digital transformation process in the healthcare sector Keywords— Personal Health Record, Acceptance, medical record